2012
DOI: 10.1016/j.bbamcr.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The elusive middle domain of Hsp104 and ClpB: Location and function

Abstract: Hsp104 in yeast and ClpB in bacteria are homologous, hexameric AAA+ proteins and Hsp100 chaperones that function in the stress response as ring-translocases that drive protein disaggregation and reactivation. Both Hsp104 and ClpB contain a distinctive coiled-coil middle domain (MD) inserted in the first AAA+ domain, which distinguishes them from other AAA+ proteins and Hsp100 family members. Here, we focus on recent developments concerning the location and function of the MD in these hexameric molecular machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 138 publications
(315 reference statements)
2
93
0
2
Order By: Relevance
“…67,82,[151][152][153][154] Importantly, the MD is less conserved than the 2 NBDs, indicating that it can withstand various missense mutations without eliminating disaggregase functionality. 67 Indeed, the MD can even tolerate large protein insertions (e.g., insertion of lysozyme between Asn467 and Glu468 in MD helix 2) or helix replacements and yet still maintain Hsp104 disaggregase activity. 106,152,153 Moreover, previous studies suggested that Hsp104 MD variants can have unexpected gain-of-function phenotypes, including rescue of polyglutamine aggregation and toxicity.…”
Section: 2298mentioning
confidence: 99%
See 2 more Smart Citations
“…67,82,[151][152][153][154] Importantly, the MD is less conserved than the 2 NBDs, indicating that it can withstand various missense mutations without eliminating disaggregase functionality. 67 Indeed, the MD can even tolerate large protein insertions (e.g., insertion of lysozyme between Asn467 and Glu468 in MD helix 2) or helix replacements and yet still maintain Hsp104 disaggregase activity. 106,152,153 Moreover, previous studies suggested that Hsp104 MD variants can have unexpected gain-of-function phenotypes, including rescue of polyglutamine aggregation and toxicity.…”
Section: 2298mentioning
confidence: 99%
“…67,81 We focused our libraries on the coiled-coil MD, which is comprised of 4 a-helices and facilitates optimal ATPase activity, communication between NBD1 and NBD2, intrinsic disaggregase activity, and interactions with Hsp70 during disordered aggregate dissolution. 67,82,[151][152][153][154] Importantly, the MD is less conserved than the 2 NBDs, indicating that it can withstand various missense mutations without eliminating disaggregase functionality. 67 Indeed, the MD can even tolerate large protein insertions (e.g., insertion of lysozyme between Asn467 and Glu468 in MD helix 2) or helix replacements and yet still maintain Hsp104 disaggregase activity.…”
Section: 2298mentioning
confidence: 99%
See 1 more Smart Citation
“…30 The protein forms a 2-tiered hexamer with a central pore, through which substrate is threaded. 30,31 Hsp104 is very large, consisting of 6 102-kDa monomers, and its structure remains poorly understood. Therefore, Hsp104 is a relatively poor candidate for rational design.…”
Section: Strategies For Re-engineering Hsp104mentioning
confidence: 99%
“…We selected the middle domain of Hsp104 for randomization, because the middle domain facilitates ATPase activity, communication between NBD1 and NBD2, intrinsic disaggregase activity, and interactions with Hsp70. 26,30 Restricting mutations to just the middle domain was key, as limiting the size of the randomized region allowed for greater depth of coverage. Additionally, this strategy allowed for sequencing to be restricted to a length allowing a single sequencing reaction per variant.…”
Section: Strategies For Re-engineering Hsp104mentioning
confidence: 99%